Analysis of the performance of Ukrainian triple jumpers at the summer World Championships during the years of Independence - Stepanenko, Dmytro; Pechko, Hanna; Hrebeniuk, Oleh; Novak, Tetiana (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. In recent years, scientific research, in order to identify significant results, has had to take into account a large number of factors when studying a particular issue. This approach confirms the need for large-scale work on the scientific substantiation of the effectiveness of direct preparation for major international competitions, by summarizing modern theoretical developments and practical experience in the preparation of national teams that occupy the first positions at the Olympic Games and world championships. That is why the current state of development of a particular sport should begin with an analysis of the effectiveness of the performances of Ukrainian athletes at the highest level competitions. Purpose of the study: to study the dynamics of sports results of Ukrainian triple jumpers at the summer world championships during the period of independence. Material and methods. In the course of the presented study, the following methods were used: theoretical analysis and generalization of data from scientific and methodological literature, analysis of competition protocols, pedagogical observation, methods of mathematical statistics. Results. An analysis of the performances of the strongest triple jumpers of Ukraine at the summer world championships during the period of independence of our state was conducted. It was established that the men’s team was represented in this type of athletics at 50% of the world championship competitions, and the women’s team at 14 of the 16 summer world championships held. During the studied period, the women’s team has two gold, one silver and two bronze medals in its achievements, as well as a world record, while the best performance of the men’s team is limited to 9th place, which is unsatisfactory. Conclusions. The results of the study confirm the existence of a problem in implementing the acquired level of sports form in the main competitions of the season using the example of the summer world championships. The men’s national team of Ukraine in athletics was represented only at half of the world championships held during the years of independence, and only in 20% of cases, the athletes managed to show a high result, which indicates the presence of shortcomings in the construction of direct preparation of athletes for the main competitions.